The Role of Ectonucleotidases CD39 and CD73 and Adenosine Signaling in Solid Organ Transplantation - Roberts, Veena; Stagg, John; Dwyer, Karen M. (Frontiers in Immunology, 2014)
Extracellular adenosine is a potent immunomodulatory molecule that accumulates in states of inflammation. Nucleotides such as adenosine triphosphate (ATP) and adenosine diphosphate (ADP) are release from injured and necrotic cells and hydrolysed to adenosine monophosphate (AMP) and adenosine by the concerted action of the ectonucleotidases CD39 and CD73. Accumulating evidence suggest that purinergic signaling is involved in the inflammatory response that accompanies acute rejection and chronic allograft dysfunction. Modification of the purinergic pathway has been shown to alter graft survival in a number of solid organ transplant models and the response to ischemia-reperfusion injury (IRI). Furthermore the purinergic pathway is intrinsically involved in B and T cell biology and function. Although T cells have traditionally been considered the orchestrators of acute allograft rejection, a role for B cells in chronic allograft loss is being increasingly appreciated. This review focuses on the role of the ectonucleotidases CD39 and CD73 and adenosine signalling in solid organ transplantation including the effects on IRI and T and B cell biology.